The mechanical patient : finding a more human model of health - Glouberman, Sholom; Taylor and Francis (Boca Raton, FL : Productivity Press, an imprint of Taylor and Francis, 2018)
Healthcare is very much dependent on the model of the patient that is assumed by healthcare providers. The current model derives from a chemical/mechanical view of the patient body. Simply put: we are healthy if all of our mechanical parts are working properly and if all of the chemicals in our body are in the right proportions and have the appropriate reactions. This view is based on philosophical accounts of the body that go back to Paracelsus, Descartes, Boyle and others. It became the central basis of medical practice only in the late 19th Century after several hundred years of research and professional politics.
chapter 1 Introduction -- chapter 2 Aristotle and a Good Life -- chapter 3 Galen s Four Humors: The First Medical Model -- chapter 4 The Renaissance and Roots of the Mechanical Patient -- chapter 5 Robert Boyle: The First Mechanical Patient -- chapter 6 The Story of Scurvy and the First Failed Controlled Trial -- chapter 7 Surgery and the Mechanical Patient -- chapter 8 Medicine and the Chemical Patient -- chapter 9 Genetics and the Return of Individualized Medicine -- chapter 10 The Great Mortality Shift -- chapter 11 Humanizing Health: The Social/Relational Person.
Keywords: BUSINESS & ECONOMICS / Production & Operations Management; Business, Management and Accounting; Health -- History; Health; Medicine -- Philosophy; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy